2020
DOI: 10.3390/ijms21217968
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenoceptor Activation in Breast MCF-10A Cells Induces a Pattern of Catecholamine Production Similar to that of Tumorigenic MCF-7 Cells

Abstract: Adrenaline, which participates in the neuroendocrine response that occurs during stress and perimenopause, may be tumorigenic. This exploratory study aimed at investigating whether non-tumorigenic and tumorigenic human breast epithelial cell lines are able to synthesize adrenaline. The study was carried out in non-tumorigenic (MCF-10A) and tumorigenic (MCF-7) human breast cell lines. Expression of enzymes involved in adrenaline synthesis was characterized by RT-qPCR, immunocytochemistry and western blot. Catec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 67 publications
4
20
0
Order By: Relevance
“…The observation and morphological analysis of the cells treated with the different concentrations of this established antineoplastic agent was also carried out (Figure 5). Analyzing the obtained curve, it is possible to conclude that, in agreement with our previous work [15], with the seeding density of 2.3 × 10 4 cells/mL (4600 cells/well), the cells remained in the exponential growth phase during the experiments, ensuring the stability and viability of MCF-7 cells.…”
Section: Effect Of Paclitaxel On Mcf-7 Cellular Viabilitysupporting
confidence: 87%
See 1 more Smart Citation
“…The observation and morphological analysis of the cells treated with the different concentrations of this established antineoplastic agent was also carried out (Figure 5). Analyzing the obtained curve, it is possible to conclude that, in agreement with our previous work [15], with the seeding density of 2.3 × 10 4 cells/mL (4600 cells/well), the cells remained in the exponential growth phase during the experiments, ensuring the stability and viability of MCF-7 cells.…”
Section: Effect Of Paclitaxel On Mcf-7 Cellular Viabilitysupporting
confidence: 87%
“…With Recently, our group reported that three drugs that interact with the adrenergic system (ICI 118,551, isoprenaline, and propranolol; Table 1) influence the proliferation of breast cells (tumorigenic MCF-7 cells) and their ability to produce adrenaline. It was observed that these cells have the potential to synthesize and release adrenaline, influenced by the exposure to agonists/antagonists of β-adrenoreceptors [15]. Indeed, evidence from the literature suggests the presence of β-adrenoreceptors in cancer cells, important for different processes of initiation and progression of the disease [16].…”
Section: Introductionmentioning
confidence: 99%
“…produce noradrenaline and acquisition of a tumorigenic phenotype may increase the capacity of breast cells to go further in the catecholamine biosynthetic pathway, increasing the capacity to transform noradrenaline in adrenaline, as recently reported by our research group (Amaro et al, 2020). These locally produced catecholamines may potentiate the adrenergic capacity to promote carcinogenesis creating an adrenergic influence of the tumor autonomous from catecholamines produced elsewhere.…”
Section: The Adrenergic System In the Breast Tumor Microenvironmentsupporting
confidence: 61%
“…Zhou et al, 2016). The adrenergic modulation of the immune response to breast cancer can even be more oriented than previously expected, having in mind the recent finding that cancer cells may produce locally adrenaline, making the adrenergic contribution for the immunosuppressive tumor microenvironment even more efficient and less dependent from SNS stimulation and from plasma catecholamines (Amaro et al, 2020).…”
Section: Adrenergic Modulation Of the Immune Responsementioning
confidence: 99%
“…The involvement of yohimbine in inflammatory and metastatic pathways has encouraged researchers to evaluate its anticancer potential. Activation of the sympathetic nerves and increased plasma catecholamines indicates higher risk and lower survival of cancer patients due to activated stress response mechanisms [ 92 , 93 ]. Noradrenaline and adrenaline typically orchestrate acute stress reactions and promote other biological processes favourable for stimulating cancer cell proliferation and inhibiting immune surveillance [ 94 ].…”
Section: Introductionmentioning
confidence: 99%